Linseed supplementation during uterine and early post-natal life markedly affects fatty acid profiles of brain, liver and muscle of lambs. Issue 1 (31st December 2022) - Nudda, Anna; Bee, Giuseppe; Correddu, Fabio; Lunesu, Mondina Francesca; Cesarani, Alberto; Rassu, Salvatore Pier Giacomo; Pulina, Giuseppe; Battacone, Gianni
Abstract: This study investigated the effects of maternal linseed supplementation during gestation and lactation on muscle, brain and liver tissues composition and fatty acid (FA) profile in lambs. In a 2 × 2 factorial design, a total of 36 Sarda dairy ewes were fed a control diet (CON, n = 18) or a diet containing linseed (LIN, n = 18) during the last 8 weeks of gestation. After lambing, 9 ewes per group changed to the other diet, moving from CON to LIN and vice-versa. The single-born lambs ( n = 36) were reared exclusively on milk and were slaughtered at 4 weeks of age and samples of muscle, brain, and liver tissues were collected. Data were analysed with a general linear model to test the effects of mothers' gestation and lactation diets, their interaction and the effect of lamb sex. Experimental results evidenced that lambs from mothers fed LIN diet during lactation had a greater content of almost all C18:1 and conjugated linoleic acid (CLA) isomers, both in muscle ( P < .01) and in the liver ( P < .05), than those from mothers fed CON. Linseed supplementation during gestation generally increased the content of C22:5n3 ( P < .01) and C22:6n3 in the brain. In conclusion, experimental results evidenced that the supplementation of ewes' diet with linseed during lactation strongly affected the muscle and liver FA profile of lambs. The effect of linseed was effective also during gestation, especially on brain tissue, but to a minor extent. Highlights: Results of the present work confirm the large impact of maternal diet on the fatty acid composition of lamb tissues Linseed supplementation during gestation generally increased the content of PUFA n3 in the brain of lambs Linseed supplementation of mothers during lactation affects the muscle and liver FA profile of sucking lambs